Risk factors for renal impairment revealed after unilateral adrenalectomy in patients with primary aldosteronism. Issue 27 (July 2016) - Kim, Do Hee; Kwon, Hee Jin; Ji, Sang A.; Jang, Hye Ryoun; Jung, Sin-Ho; Kim, Jung-Han; Kim, Jae Hyeon; Lee, Jung Eun; Huh, Wooseong; Kim, Yoon-Goo; Kim, Dae Joong; Oh, Ha Young
Abstract : Abstract: Primary aldosteronism (PA) may induce significant decline of renal function and structural damage of kidney. However, it is difficult to evaluate accurate renal function in patients with PA, because glomerular hyperfiltration and aldosterone escape can conceal renal impairment. In this retrospective cohort study, we compared changes in renal function after unilateral adrenalectomy between patients with PA and patients with other adrenal diseases. Risk factors associated with postoperative renal impairment in patients with PA were analyzed. A total of 558 patients who received unilateral adrenalectomy between January 2002 and June 2013 were included: 136 patients with PA and 422 patients with other adrenal diseases (control). Postoperative serial changes in estimated glomerular filtration rate (eGFR) were analyzed in both groups. Multivariate analyses were performed to identify risk factors of renal impairment after adrenalectomy in all patients and the PA group. Postoperative renal impairment was defined as postoperative eGFR decline of >25% from preoperative eGFR. Chronic kidney disease (CKD) was defined as an eGFR <60 mL/min/1.73 m 2 . There were no differences in preoperative eGFR between groups. The PA group showed a significant decrease in eGFR 3 days, 2 weeks, and 6 months after surgery compared to the control group. The PA group showed significant improvement of hypertension after surgery. In the PA group, 53 (39.0%) patients showed postoperative renal impairment. Multivariate regression analysis identified long-standing hypertension, low body mass index, low serum potassium, and high preoperative eGFR as risk factors for postoperative renal impairment. Among the 89 patients with preoperative eGFR ≥60 mL/min/1.73 m 2, 29 (32.6%) patients developed CKD postoperatively. Age, low serum potassium, low preoperative eGFR, and high serum cholesterol or uric acid were associated with the postoperative CKD development. Our study demonstrates that patients with PA with old age, low serum potassium, long-standing hypertension, and high serum uric acid or cholesterol are at risk of renal impairment after surgical treatment. High preoperative eGFR was also a risk factor for postoperative renal impairment, whereas low preoperative eGFR was a risk factor for postoperative CKD. Close monitoring of renal function and adequate management are required for patients with these risk factors. Abstract : Supplemental Digital Content is available in the text